2016
DOI: 10.1007/s11906-016-0689-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Hypertension and the Sex Hormone Paradox

Abstract: Female sex has been shown to be a risk factor for the development of PAH, but women have improved survival compared to men with PAH. These paradoxical observations are likely driven in part by complex sex hormone signaling and processing pathways and their interaction with the pulmonary vasculature and the right ventricle. These relationships may vary depending on an individual's underlying sex, age, and/or genetic substrate. The study of the connections between sex, sex hormones, the pulmonary circulation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 68 publications
1
31
0
Order By: Relevance
“…All the animals included in this study were male rats. Given that PAH is a disease that afflicts females almost twice more than men [39], future studies should include female animals. Finally, our strain-energy analysis did not account for the prestretch of the matrix and consequent precompression of the myocytes in the intact myocardium.…”
Section: Limitationsmentioning
confidence: 99%
“…All the animals included in this study were male rats. Given that PAH is a disease that afflicts females almost twice more than men [39], future studies should include female animals. Finally, our strain-energy analysis did not account for the prestretch of the matrix and consequent precompression of the myocytes in the intact myocardium.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, the study was only limited to male rats. Even though the incidence of PAH in women is almost twice as in men (Foderaro and Ventetuolo ), a study by Ventetuolo et al. () reported that female patients have a better survival than male patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study was only limited to male rats. Even though the incidence of PAH in women is almost twice as in men (Foderaro and Ventetuolo 2016), a study by Ventetuolo et al (2014) reported that female patients have a better survival than male patients. Furthermore, while PAH incidence is higher in females than in males, rodent models of PAH have suggested that estrogen play an important role in the pulmonary vasculature, producing beneficial effects in response to PAH (Pugh and Hemnes 2010).…”
Section: Limitationsmentioning
confidence: 98%
“…Significant evidence suggest that production of sex steroids is also found in peripheral tissues of non-reproductive organs, such as the adrenal gland, heart, breast, and lung implying a dependency on the enzymes present in the organs [120,121]. It is thought that the source of hormone production can affect the metabolism, circulation, regulation, and concentration of local steroid versus that of circulation, which can play a role in the paradoxical effects observed for some sex hormones [43,122,123]. One example is the "estrogen paradox", observed in women with pulmonary hypertension.…”
Section: Sex Hormones and Lung Immunity 41 Sex Hormones And Mechanimentioning
confidence: 99%